2002
DOI: 10.1094/pdis.2002.86.11.1206
|View full text |Cite
|
Sign up to set email alerts
|

Citrus and Coffee Strains of Xylella fastidiosa Induce Pierce's Disease in Grapevine

Abstract: Xylella fastidiosa causes citrus variegated chlorosis (CVC) disease in Brazil and Pierce's disease of grapevines in the United States. Both of these diseases cause significant production problems in the respective industries. The recent establishment of the glassy-winged sharpshooter in California has radically increased the threat posed by Pierce's disease to California viticulture. Populations of this insect reach very high levels in citrus groves in California and move from the orchards into the vineyards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
0
26
1
9
Order By: Relevance
“…Nas diferentes áreas vitícolas do sul do Brasil, é comum o plantio de citros nas bordaduras dos parreirais e não menos frequente, os mesmos são cercados por pomares de ameixa, culturas geralmente infectadas pela bactéria X. fastidiosa. Eventualmente, essa prática pode resultar na infecção de videira com X. fastidiosa por meio de transmissão cruzada, na qual cigarrinhas vetoras adquirem a bactéria em outros hospedeiros, inoculando-a nas plantas de videira (Perring et al 2001, Li et al 2002, Bi et al 2007. Esse risco existe, pois as cigarrinhas B. xanthophis, P.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Nas diferentes áreas vitícolas do sul do Brasil, é comum o plantio de citros nas bordaduras dos parreirais e não menos frequente, os mesmos são cercados por pomares de ameixa, culturas geralmente infectadas pela bactéria X. fastidiosa. Eventualmente, essa prática pode resultar na infecção de videira com X. fastidiosa por meio de transmissão cruzada, na qual cigarrinhas vetoras adquirem a bactéria em outros hospedeiros, inoculando-a nas plantas de videira (Perring et al 2001, Li et al 2002, Bi et al 2007. Esse risco existe, pois as cigarrinhas B. xanthophis, P.…”
Section: Resultsunclassified
“…Os cartões adesivos foram triados em laboratório quantifi cando-se e identifi cando-se os espécimes capturados com emprego de chaves dicotômicas (Young 1968, 1977, Emmrich 1984, Marucci et al 1999, Azevedo Filho & Carvalho 2001a, b, 2002, 2006 e por comparação direta de exemplares. Espécimes de referência de cada espécie foram depositados na coleção entomológica da Embrapa Uva e Vinho, Bento Gonçalves, RS (Azevedo Filho et al 2007).…”
Section: Método De Levantamentounclassified
See 1 more Smart Citation
“…Yet, genetic studies have shown that X. fastidiosa isolates from citrus and coffee cluster separately from each other although they form a monophyletic group (Costa et al, 2000;Qin et al, 2001;Martinati et al, 2005). Interestingly, Li et al (2001) were able to infect coffee plants and observe CSA-like symptoms after inoculation with an isolate originally from citrus, suggesting the possibility of cross-infection by these strains. Li et al (2002) also showed that both CVC and CSA isolates can cause symptoms of Pierce's Disease in grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Li et al (2001) were able to infect coffee plants and observe CSA-like symptoms after inoculation with an isolate originally from citrus, suggesting the possibility of cross-infection by these strains. Li et al (2002) also showed that both CVC and CSA isolates can cause symptoms of Pierce's Disease in grapevine. In addition, Lopes et al (2003) demonstrated that CVC and CSA isolates had similar colonization patterns in various weed host plants.…”
Section: Introductionmentioning
confidence: 99%